European Traditions in Didactics of Mathematics - Blum, Werner; Artigue, Michèle; Mariotti, Maria Alessandra; Sträßer, Rudolf; Van den Heuvel-Panhuizen, Marja (ICME-13 Monographs, 2019)
This open access book discusses several didactic traditions in mathematics education in countries across Europe, including France, the Netherlands, Italy, Germany, the Czech and Slovakian Republics, and the Scandinavian states. It shows that while they all share common features both in the practice of learning and teaching at school and in research and development, they each have special features due to specific historical and cultural developments. The book also presents interesting historical facts about these didactic traditions, the theories and examples developed in these countries.